ANTIOXIDANT POTENTIAL TEST OF ETHANOL EXTRACT OF MIMOSA PUDICA LINN AS HERBAL MEDICINE INGREDIENTS - Ni Made Devi Damayanti; I Wayan Sudira; Wayan Bebas; Luh Made Sudimartini; Yudha Yaksa Crada Yoga Arum Raharjo (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
neutralize free radicals. Mimosa pudica Linn. leaves have advantages as herbal medicine ingredients. Through phytochemical screening, mimosa pudica contains antioxidant compounds such as alkaloids, phenols, steroids, flavonoids, and saponins. This study aims to determine the antioxidant potential of mimosa pudica leaves as herbal medicine ingredients. Using the antioxidant capacity and IC50% methods with concentrations of 0 mg/ml, 0.01 mg/ml, 0.029 mg/ml, 0.44 mg/ml, 0.73 mg/ml with a wavelength of 517 nm, testing using a spectrophotometer. The highest results were obtained from a concentration of 10 ppm, which was 64.326% and the final result of the IC50% test was 57.58 ppm. Based on the results obtained, it can be seen that the ethanol extract of mimosa pudica leaves has strong antioxidant activity. It is necessary to conduct further and deeper research on mimosa leaves using other methods to find out how well mimosa leaves can be used in the world of health, considering that mimosa leaves are easy to find.